2020
DOI: 10.1097/aog.0000000000003787
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Approval of 17α-Hydroxyprogesterone Caproate

Abstract: Before 2011, 17α-hydroxyprogesterone caproate (17P) was used to prevent recurrent preterm birth in women with singleton pregnancies and was compounded at a low cost (∼$15 per injection). In 2011, the U.S. Food and Drug Administration (FDA) approved a commercial version of 17P (trade name “Makena”) through their Accelerated Approval Program, and the price of 17P subsequently increased by nearly 100-fold. This approval was largely based on a methodologically limited, placebo-controlled trial, which found that al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…A large multicenter international study under the direction of the Pregnancy Research Branch of NIH based at Wayne State University demonstrated significant efficacy of such suppositories [69][70][71][72][73][74][75]. Despite that, the US Preventative Services Task Force (USPTF) refused to endorse their use after performing a very unconventional and convoluted statistical analysis in which the USPTF ignored significant components of the study data and focused on only a subset (following the findings of one US-based center rather than the findings of three European centers) [69][70][71][72][73][74][75]. Concurrently, a company produced Makena and obtained FDA approval for weekly injections of 17α-hydroxyprogesterone caproate under an Accelerated Approval Program -set up to permit rapid development of drugs that addressed serious medical problems.…”
Section: -Ohpcmentioning
confidence: 99%
See 2 more Smart Citations
“…A large multicenter international study under the direction of the Pregnancy Research Branch of NIH based at Wayne State University demonstrated significant efficacy of such suppositories [69][70][71][72][73][74][75]. Despite that, the US Preventative Services Task Force (USPTF) refused to endorse their use after performing a very unconventional and convoluted statistical analysis in which the USPTF ignored significant components of the study data and focused on only a subset (following the findings of one US-based center rather than the findings of three European centers) [69][70][71][72][73][74][75]. Concurrently, a company produced Makena and obtained FDA approval for weekly injections of 17α-hydroxyprogesterone caproate under an Accelerated Approval Program -set up to permit rapid development of drugs that addressed serious medical problems.…”
Section: -Ohpcmentioning
confidence: 99%
“…Assessment of PTB treatments requires multiple levels of queries. First, the idea that a serious problem like PTB, with risks in part determined by a multitude of social determinants of health, could be treated as a single problem amenable to any single therapy is certainly not a given [69][70][71][72][73][74][75]. Second, the variability in quality of compounded treatments (which are not as tightly controlled as pharmaceutical company products but in which physicians had considerable confidence) needed to be understood.…”
Section: -Ohpcmentioning
confidence: 99%
See 1 more Smart Citation